Water Buffalo (Bubalus bubalis) and their Technological Advantages for the Design in Healthy Meat Product - Rey, J. F.; Povea, I. E. (Journal of Buffalo Science, 2012)
Current trends in the formulation for new food shows that healthy or â€œfunctionalâ€ products are graduallyincreasing their participation in the preference of the consumers (Catalá Ramón). Nowadays, the participation of meatproducts in this behavior of the marketing is not growing at the same rate, because their ingredients and nutritionalcompounds, like saturated fats, which are rejected by consumers. But, a group of investigators from La Salle University(Universidad De La Salle, Bogotá, Colombia), have been working hard, in order to obtain healthier meat products, usingBufalo as the main raw material, because its important properties like 15 to 35% of protein, 40% more water holdingcapacity (CRA, in Spanish) and 30% more emulsifying capacity (CE in Spanish). Previous values are compared with rawbeef. The group, who has developed a functional buffalo meat product, added vegetal oil from soybeans and dehydratedhemoglobin to its formulation and obtained a food with 70% less of saturated fat and a significantly increase of iron,without affecting the non-saturated fat compound of the food. Now, a functional product packed in a "smart packaging" has been studied, in order to increase its shelf life, supported on positive migration process.